2018
DOI: 10.1021/acsaem.7b00174
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Performance of Single Phase p-Type Quaternary (PbTe)0.65–x(PbSe)0.35(PbS)x Alloys

Abstract: Recently, the quaternary system PbTe-PbSe-PbS has been shown to provide high thermoelectric efficiency, zT. The intent of this research is to investigate the thermoelectric properties of Na-doped pseudoternary (PbTe) 0.65-x (PbSe) 0.35 (PbS) x with a high ratio of PbS toPbTe. The addition of a large concentration of PbSe increases the solubility limit of PbS in PbTe, allowing all samples to behave as solid solutions with a high concentration of PbS. This is proved to decrease lattice thermal conductivity due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The current samples exhibit lower κ latt than the single-phase Na-doped compounds (PbTe) 0.65 (PbS) 0.25 (PbSe) 0.1 24 and (PbTe) 0.9 (PbSe) 0.1 , 23 as well as Na-doped PbTe below 600 K, 34 and κ latt of our samples is comparable to that of the multiphase nanostructured compound Pb 0.985 Na 0.015 Se 0.1 S 0.25 Te 0.65 25 and the single-phase compound Pb 0.98 Na 0.02 Se 0.1 S 0.05 Te 0.85 . 24 The microscopy analysis of single-phase polycrystalline Pb chalcogenides (with similar composition to those in the current study) shows no significant microstructural changes with slight compositional variations; 35 thus, the significantly reduced κ latt in our single-phase compound can be attributed to enhanced phonon scattering arising from randomly distributed Se and S solute atoms in the matrix.…”
Section: Resultssupporting
confidence: 69%
“…The current samples exhibit lower κ latt than the single-phase Na-doped compounds (PbTe) 0.65 (PbS) 0.25 (PbSe) 0.1 24 and (PbTe) 0.9 (PbSe) 0.1 , 23 as well as Na-doped PbTe below 600 K, 34 and κ latt of our samples is comparable to that of the multiphase nanostructured compound Pb 0.985 Na 0.015 Se 0.1 S 0.25 Te 0.65 25 and the single-phase compound Pb 0.98 Na 0.02 Se 0.1 S 0.05 Te 0.85 . 24 The microscopy analysis of single-phase polycrystalline Pb chalcogenides (with similar composition to those in the current study) shows no significant microstructural changes with slight compositional variations; 35 thus, the significantly reduced κ latt in our single-phase compound can be attributed to enhanced phonon scattering arising from randomly distributed Se and S solute atoms in the matrix.…”
Section: Resultssupporting
confidence: 69%
“…These approaches have been frequently proven to be successful for advancing thermoelectrics, especially in p-type IV-VI compounds [16,[39][40][41][42][43][44][45][46][47]. Manipulation of the energy offset between the light valence band (L) and the heavy valence band (Σ) via alloying enables charge carriers to be transported by many band valleys (band degeneracy) for an increase in σ without explicitly reducing S [48].…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been established for many isovalent-element-doped thermoelectric materials. [21][22][23][24][25][26][27][28][29][30] In this study, we investigated the electrical and thermal transport properties of isovalent Cu-and Sn-doped Ag 6 Ge 10 P 12 . It was revealed that the lattice thermal conductivity of Ag 6 Ge 10 P 12 can be systematically reduced by substitution the isovalent elements Cu and Sn for Ag and Ge, respectively.…”
Section: Introductionmentioning
confidence: 99%